2011
DOI: 10.1007/s11434-011-4528-6
|View full text |Cite
|
Sign up to set email alerts
|

Motion speed modulates walking direction discrimination: The role of the feet in biological motion perception

Abstract: The human visual system is tuned to the motions of biological entities, which provide potentially vital information for survival. The current study examines the interplay between motion speed and motion direction perception. Following a brief presentation of a point-light walker walking straight ahead or slightly leftward or rightward, observers were asked to quickly judge the walking direction (left or right). Participants showed better direction discrimination when the walker walked at a fast pace compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…There has been considerable research on the effects of speed modulation on the processing of biological motion in humans (e.g. Kozlowski and Cutting 1977 ; Barclay et al 1978 ; Lange and Lappe 2006 ; Watanabe 2008 ; Cai et al 2011 ). Barclay et al ( 1978 ) examined how variations in walking speed (normal or slow speed) affected the recognition of gender.…”
Section: Methodsmentioning
confidence: 99%
“…There has been considerable research on the effects of speed modulation on the processing of biological motion in humans (e.g. Kozlowski and Cutting 1977 ; Barclay et al 1978 ; Lange and Lappe 2006 ; Watanabe 2008 ; Cai et al 2011 ). Barclay et al ( 1978 ) examined how variations in walking speed (normal or slow speed) affected the recognition of gender.…”
Section: Methodsmentioning
confidence: 99%
“…We hence examined this issue using a typical task on walking direction discrimination which has been widely adopted to explore biological motion perception (Cai, Yang, Chen, & Jiang, ; Chang & Troje, ; Gurnsey, Roddy, & Troje, ; Jiang & He, ; Kuhlmeier, Troje, & Lee, ; Saunders, Williamson, & Troje, ; Sweeny et al., ). Previous studies have explored the influence of low‐level stimulus properties, such as motion speed, on walking direction discrimination; the current study focused on the potential role of social and biological properties in the perception of walking direction.…”
mentioning
confidence: 99%
“…We aimed to further examine the effects of walker gender and observer gender on biological motion walking direction discrimination. In comparison with the ambiguous in‐depth facing orientation judgment, the task on walking direction discrimination is considered a basic perceptual process of the visual system, and is less susceptible to response bias (Aaen‐Stockdale, Thompson, Hess, & Troje, ; Cai et al., ; Neri et al., ; Shi et al., ; Thompson et al., ; Thornton & Vuong, ; Troje & Westhoff, ). Even 6‐month‐old infants have been reported to possess the ability to differentiate the walking direction of an upright human point‐light walker (left vs. right; Kuhlmeier et al., ).…”
mentioning
confidence: 99%
“…This is particularly relevant since, also in our species, the speed of movement can drastically alter the perception of biological motion, with abnormal speeds giving the impression of unnatural (e.g., robotic or moon-walk) movements (Barclay et al, 1978 ). Moreover, both humans (Kozlowski and Cutting, 1977 ; Barclay et al, 1978 ; Cai et al, 2011 ) and the fish tested by Nakayasu and Watanabe ( 2014 ) seem to be more affected if the movement sequences were slowed down than if velocity was increased.…”
Section: Second Order Motion and Biological Motionmentioning
confidence: 99%
“…Another crucial aspect highlighted by research in fish is the similarity in the characteristics of the effects observed in distant classes of vertebrates. For example, both in fish and in humans the perception of Kanizsa figures is disrupted by the same manipulation (von der Heydt, 2004 ; Wyzisk and Neumeyer, 2007 ), and the perception of biological motion is similarly affected by changes in speed (Kozlowski and Cutting, 1977 ; Barclay et al, 1978 ; Cai et al, 2011 ; Nakayasu and Watanabe, 2014 ). These remarkable similarities may indicate an analogous organization, in distant vertebrates, of the neural circuitry involved in these perceptual effects.…”
Section: Conclusive Remarksmentioning
confidence: 99%